2016
DOI: 10.1044/2015_ajslp-13-0137
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Sound Level Meter Apps in the Clinical Setting

Abstract: The use of apps for SPL readings in the clinical setting is premature because all 3 apps adopted were incomparable with the Type 1 SLM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Because the microphones are different across devices, it is expected that the mean results will vary. In fact, the results from the current study were similar to Fava and colleagues (2016) when only looking at the main effect of device. In the current study, there were differences in the means of some of the voice measures across the smartphones and the head mounted microphone.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Because the microphones are different across devices, it is expected that the mean results will vary. In fact, the results from the current study were similar to Fava and colleagues (2016) when only looking at the main effect of device. In the current study, there were differences in the means of some of the voice measures across the smartphones and the head mounted microphone.…”
Section: Discussionsupporting
confidence: 81%
“…Results indicated that three SLM apps on an iPhone 5 and a RadioShack (Fort Worth, TX) SLM yielded inconsistent dB readings for the human voice at soft, habitual, and loud when compared with a Type 1 SLM. Frankly, it is not surprising that the results in Fava and colleagues (2016) were significantly different across recording devices for the human voice recordings and outside of the established criterion of ± 2dB. The procedures did not account for within subject variability across trials.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…With recent technological advancements (e.g., portable tablet computers and multimedia players), sound level meters (SLMs) have become widely accessible for clinical use for voice and speech assessment. For example, using mobile phone applications (apps) for SLM readings is cost and time efficient, technologically advanced, portable, and engaging for patients and clinicians (Fava et al, 2016). Although a review of the literature supports the general effectiveness of using handheld technology as an augmentative and alternative communication system for children with ASD (Gilroy et al, 2017;Goldsmith & LeBlanc, 2004;Lorah et al, 2015Lorah et al, , 2018, researchers seldom evaluate transportable technology on different aspects of communication, such as acoustic output.…”
mentioning
confidence: 99%
“…18 Few clinical studies have compared the performance of sound measurement systems that include smartphones and SLMAs using different features, stimuli, and acoustic environments. Fava et al 19 determined that their use of three uncalibrated SLMAs in an anechoic chamber resulted in inconsistent measures of pure tones (125, 250, 500, 1,000, 2,000, 4,000, and 8,000 Hz) from 60 to 100 dB SPL compared with a Type 1 SLM, and were inaccurate for human voice and vocal intensity measurements > 50 dB SPL. However, Serpanos et al 20 found that SLMAs using calibrated internal smartphone microphones were accurate for measuring narrow band noise and white noise (WN) at levels > 40 dBA in a sound-treated test booth.…”
mentioning
confidence: 99%